The Impact of Intellectual Capital on Firms’ Characteristics: An Empirical Analysis on European Listed Manufacturing Companies - Iazzolino, Gianpaolo; Migliano, Giuseppe; Dattilo, Maria Ida (International Journal of Industrial Engineering and Management, 2019)
This work aims at advancing knowledge about the relationship among Intellectual Capital (IC), firms’ performances and market value by investigating 10-year data gathered from a sample of manufacturing companies listed on the Euronext Stock Exchange. An exploratory study was designed to: (i) highlight linkages amidst the IC components and (ii) show the consistence of the ties amongst IC, financial performance and firm’s value variables. Findings highlighted that: (i) Structural Capital (SC) and Relational Capital (RC) impacted directly on firms’ performances and that (ii) only SC, within a certain time horizon, had significant effects on firms’ market value. The research demonstrates that, even in the manufacturing industry, IC can have an important impact on performances. This study could be useful for scholars, who aims at deepening knowledge about the linkage between IC and financials, and for practitioners, to figure out how investments in Intellectual Capital should be addressed to get better financial performances and a higher market value. Article history: Received (05-MAR-2019); Revised (04-SEP-2019); Accepted (6-SEP-2019); Published online (9-SEP-2019)